Can oral health care be a gateway to improve cardiovascular disease? A scoping review - Usmani, Wania; de Courten, Maximilian; Hanna, Fahad (Frontiers in Oral Health, 2024)
Background: Cardiovascular diseases (CVDs) are a significant cause of morbidity and mortality worldwide, resulting in a high socioeconomic burden. Growing evidence has shown a link between oral diseases and several chronic conditions including CVDs. The focus of this review is to investigate and summarise the evidence surrounding oral health interventions and their potential impact on reducing both the risk and/or severity of CVDs.Methods: A scoping review was conducted to examine oral health interventions for managing cardiovascular disease (CVD) outcomes and risks. The review adhered to the Joanna Briggs Institute (JBI) framework for evidence synthesis and followed the reporting standards outlined by the Preferred Reporting Items for Systematic Reviews and Meta-analysis-extension to Scoping Review (PRISMA-ScR).A systematic search across EBSCOhost, PubMed, and Scopus databases from 2012 to 2024 was utilized to identify relevant studies. Inclusion criteria focused on English-language articles with a sample size of at least 50, evaluating the impact of oral health interventions on CVD outcomes.Results: Out of the initial 2154 studies identified in the search, 12 studies met the inclusion and exclusion criteria and were included in the final analysis. Overall, the studies revealed that along with surgical and non-surgical periodontal therapy, regular oral hygiene care practices, including toothbrushing, tongue brushing, and flossing, significantly reduced the risk of cardiovascular events and mortality. These interventions in patients with or without CVD baseline have shown a decrease in CVD risk markers as well as a reduction in bacterial colonization. Similarly, consistent oral hygiene routines, combined with regular dental visits, were associated with a lower risk of heart failure and CVD risk mortality.The evidence extracted from this review suggests that periodontal therapy, regular dental cleaning and re-enforcing of oral health regimes can stabilize oral health conditions and subsequently improve CVD progression/risks. However, limited to no evidence exists regarding the therapeutic effects of oral health promotion in managing CVD markers and its direct impact on disease outcomes, warranting further investigation.